On a test statistic connected with the multivariate Behrens - Fisher problem - Gupta, A.; Nagar, D. (Rev. Téc. Fac. Ing. Univ. Zulia)
The exact null distribution of a test statistic proponed earlier for testing equality to two mean vectors under the intraclass correlation models has been derived in terms of generalized hypergeometric function as well as in series form suitable for computation. Explicit expressions of the density are given for p = 2, 3, 4 and 5.